In Vitro Evaluation of Dimensional Stability of Alginate Impressions after Disinfection by Spray and Immersion Methods - Fahimeh Hamedi Rad; Tahereh Ghaffari; Sayed Hamed Safavi (Tabriz University of Medical Sciences, 2010)
Background and aims. The most common method for alginate impression disinfection is spraying it with disinfecting agents, but some studies have shown that these impressions can be immersed, too. The aim of this study was to evaluate the dimensional stability of alginate impressions following disinfecting by spray and immersion methods. Materials and methods. Four common disinfecting agents (Sodium Hypochlorite, Micro 10, Glutaraldehyde and Deconex) were selected and the impressions (n=108) were divided into four groups (n=24) and eight subgroups (n=12) for disinfecting by any of the four above-mentioned agents by spray or immersion methods. The control group (n=12) was not disinfected. Then the impressions were poured by type III Dental Stone Plaster in a standard method. The results were analyzed by descriptive methods (mean and standard deviation), t-test, two-way analysis of variance (ANOVA) and Duncan test, using SPSS 14.0 software for windows. Results. The mean changes of length and height were significant between the various groups and disinfecting methods. Regarding the length, the greatest and the least amounts were related to Deconex and Micro 10 in the immersion method, respectively. Regarding height, the greatest and the least amounts were related to Glutaraldehyde and Deconex in the immersion method, respectively. Conclusion. Disinfecting alginate impressions by Sodium Hypochlorite, Deconex and Glutaraldehyde by immersion method is not recommended and it is better to disinfect alginate impressions by spraying of Micro 10, Sodium Hypochlorite, Glutaraldehyde and immersion in Micro 10.